Pentingnya Interior Playgroup dalam Mengoptimalkan Kreativitas Anak Prasekolah - Latif, Fauzia (Humaniora, 2014)
Preschool age is a period of a child experiencing the early stage of self-development, influenced by both her/himself and surrounding environment. Playgroup is a very essential container in training children?s early stage of self-development to adulthood. It is strongly influenced by the design of the playgroup space. Good design of playgroup space will be able to optimize creativity and stimulates motoric nerves and children?s psychological side to keep learning, grow, and do activities. Creativity accompanied with intelligence and sense of responsibility is expected to make the child as excelent human being who is able to do original works and live in independence in the future.